Analysis and Evaluation of Final Examination Paper of Medical Record Informatics. (February 2014) - Fu, Yinghong; Nie, Lihua; Cai, Naxin
Abstract Objective. To objectively evaluate the quality and effectiveness of teaching and identify the problems in the teaching process, and to carry out the comprehensive analysis and evaluation of the final examination paper of medical record informatics. Method. The final examination paper of medical record informatics is analyzed through the education survey. Result. The average score of the examination paper is 70.6, and the examination results obey normal distribution. The examination paper has the features of moderate difficulty, general discrimination and good reliability. The proportion of easy questions is too large, and the proportion of the relatively difficult questions should be increased. Conclusion. The proportion of the relatively difficult questions on the examination paper should be increased promptly, so that the examination paper with moderate difficulty can objectively reflect the actual level of the students, thereby improving the quality of teaching.